Synthetic Analogs of Antimicrobial Peptides from Limulus Inhibit the Growth of Listeria monocytogenes by Increasing Cell Membrane Permeability and Suppressing Virulence Genes. (30th November 2022) - Xie, Haiwei; Wang, Mingyang; Wu, Zhongling; Lai, Zhantu; Luo, Liping; Lin, Fengcai; Lei, Jia
Abstract : Listeria monocytogenes is a foodborne pathogen that can cause listeriosis in humans and animals. It is of significant concern to the food industry as it can grow at low temperatures. Aggravatingly, only some of the commonly used food preservatives can effectively inhibit the growth of LM. In this study, the effectiveness of synthetic analogs of antimicrobial peptides from Limulus in inhibiting the growth of LM was studied. As determined by the Kirby–Bauer disc diffusion method, the diameters of the inhibition zones produced by the synthetic antimicrobial peptides ranged from 8.24 mm to 8.86 mm, and the minimum inhibitory concentrations (MICs) of the peptides ranged from 40 μ g/mL to 160 μ g/mL. At their MICs, initially, the synthetic antimicrobial peptides exhibited bacteriostatic effects on LM. They permeabilized the cell membrane of the bacterium and suppressed virulence genes (the inlA, prfA, and hly genes) in the bacterium. However, the bacteriostatic effects were effective only for 1 h, after which the bacterium slowly became resistant to them. After 6 h, the bacterium resumed its growth. Although cells in treatment groups resumed their growth after 6 h, the growth of the cells was inhibited compared to the growth of cells in the control group. Further studies are necessary to reduce the resistance of LM to the antibacterial effects of the synthetic antimicrobial peptides.